The successful management of Thirty-six hepatopancreatobiliary surgeries under the intensive protective arrangements during the COVID-19 pandemic - Tasa, Davood; Eslami, Pegah; Dashti, Habibollah; Nassiri Toosi, Mohsen; Zarghami, Seyed Yahya; Zarghami, Seyed Yahya; Jafarian, Ali (Acta Biomedica Atenei Parmensis, 2020)
ackground: During the pandemic of COVID-19, the overwhelm of infected patients created an exponential surge for ICU and ward beds. As a result, a major proportion of elective surgeries was postponed. However, various emergency and urgent procedures were allowed. Due to the mortality complications of hepatopancreatobiliary issues, we decided to afford urgent procedures under intensive protective arrangements. Method and results: In our ward (liver transplant), 4 ICU beds and 16 ward beds were allocated to non-COVID-19 patients. A total of 36 hepatopancreatobiliary procedures were managed for one month. All the surgeries were afforded under personal protective equipment and other intensive protective arrangements for personnel and patients. During 6 weeks following the surgery, all patients were followed up through telemedicine and no new case of COVID-19 was detected. Conclusion: In general, it appears that intensive protections could significantly reduce the number of COVID-19 incidence among patients with co-morbidities who undergo invasive procedures.